The inclusive school: its assumptions and movements - Capellini, Vera Lúcia Messias Fialho (2017)
The study develops a theoretical analysis of the inclusive school, making a parallel with the education and human development. Provides a discussion on current and relevant issues, including the values and paradigms that have guided the Brazilian education intended for students, with emphasis on those that presenting special educational needs. Emphasizes the importance of coexistence and respect for diversity, showing the need for flexibility, adaptation and modification of the school environment to offer everyone opportunities and conditions for full development in an inclusive culture perspective.